Fundamentals and applications of micro and nanofibers - Yarin, Alexander L. 1953- (Cambridge University Press, 2014)
A comprehensive exposition of micro and nanofiber forming, this text provides a unified framework of all these processes (melt and solution blowing, electrospinning, and so on) and describes their foundations, development and applications. It provides an up-to-date, in-depth physical and mathematical treatment, and discusses a wide variety of applications in different fields, including nonwovens, energy, healthcare and the military. It further highlights the challenges and outstanding issues from an interdisciplinary perspective of science and technology, incorporating both fundamentals and applications. Ideal for researchers, engineers and graduate students interested in the formation of micro and nanofibers and their use in functional smart materials.